A comparative analysis of morphometric changes in the angle of anterior chamber after cataract surgery - Jamil, Mahsa; ., Anupam; Samanta, Ramanuj; Mittal, Sanjeev Kumar (International Journal of Research in Medical Sciences, 2021)
Background: Cataract surgery brings about certain changes in the angle of anterior chamber and we aimed at understanding the morphometric changes occurring in the angle at the site of incision (SOI) and the site opposite to it (OSOI) after two types of cataract surgeries viz. phacoemulsification and manual small incision cataract surgery (SICS) at two postoperative follow-ups. Methods: A quasi-experimental study was conducted at AIIMS, Rishikesh and a minimum of 60 patients were enrolled. They were divided into two groups based on the surgery performed, 30 patients had undergone phacoemulsification (group A) and 30 patients had undergone SICS (group B). The patients were evaluated using optical coherence tomography (OCT), the parameters measured were central anterior chamber depth (ACD), anterior chamber angle (ACA), angle opening distance (AOD), and trabecular iris surface area (TISA). The subjects were assessed preoperatively, post-operatively at 1 week and 6 weeks. Results: The increase in the angle parameters at 1 week and 6 weeks post-operatively was found to be statistically significant in the two groups (p<0.05). The increase in the parameters was also compared between the two surgeries and was found to have no statistical difference. Conclusions: We were able to conclude that a simple cataract extraction can help treat two most common causes of blindness, cataract and glaucoma and the technique of cataract surgery used does not influence the change brought about in the angle.